Coral recruitment enhancement in fish shelter media composed of fly ash and nickel slag on Obi Island, South Halmahera - Prasari Riski Hutami; Aldico Satria Ganesa; Jesaya Alfredo Alexandro Karyoto; Windy Prayogo (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The reefcube, a modular structure, serves as a primary habitat for fish and aids in the recruitment of new coral. The reefcube is predominantly made from fly ash and nickel slag, by-products of pyrometallurgy process that contain high content of CaO, MgO, dan SiO2. These compounds aid in the calcification process of newly recruited corals. This project has been conducted since 2021, which includes deployment processes, monitoring, and data collection. The data collection methods involve randomly sampling natural coral recruits that have grown on the modular structures and measured periodicaly. So far, the coral growth ranged from 2.41 cm to 12.90 cm over the course of two years. The observed genera include Acropora, Isopora, Pocillopora, Millepora, Porites, and all of which have shown significant growth on the Reefcube. There were 24 fish families recorded during the monitoring period, with the Pomacentridae family accounting for 53% of all sightings. The most commonly observed size range was between 0-5 cm and 16-20 cm, which represented 29% and 28% of the total observations. Within this size range from Pomacentridae and Acanturidae family. Several individuals of the species Abudefduf vaigiensis from the Pomacentridae family were notably present.Keywords:Coral reef ecosystemFish shelterGrowthNickle slagReefcube